:تعليم اللغة العربية وفق الإستراتيجيات الحديثة للمراجع العالمية فن المناظرة لحلّ معضلة التحدث وتطوير مهارات التواصل = Teaching Arabic based on modern strategies of international references: debate art to solve speaking problem and develop communication skills - Chtaibi, Khalid (Mashreq International for Books Sdn Bhd, 2024)
This textbook addresses the problem of the poor speaking and communication skills among Malaysian students, despite spending a long time learning Arabic as a second language. It identifies multiple interrelated factors, including the lack of modern strategies in curricula and extracurricular activities, as well as insufficient and sustainable training for teachers and lecturers, either due to a lack of training workshops or their reluctance to participate, negatively impacting the quality of learning outcomes. The researcher aims to investigate the role and effectiveness of the art of debate as a modern strategy in accordance with international standards to improve speaking and communication skills. This is done through testing the experience of a debate club that included students from the International Islamic University and the Islamic University of Perlis in Malaysia, using a descriptive-analytical and experimental approach by collecting data and analyzing questionnaire responses from club members. The book concludes that there is a strong relationship between the presence and effectiveness of the debate club and the members' benefit in developing their communication skills, emphasizing the importance of debate as a modern strategy to address the issue of speaking and communicating in Arabic.